Broken needle in gluteal region following an intramuscular injection: a case report - Singh, Jagdeep; Kalia, Anoop; Banga, Ravinder Kumar; Dahuja, Anshul (International Journal of Research in Orthopaedics, 2019)
Incidence of broken hypodermic needle in patients has been decreased because of superior manufacturing techniques. Breaking of hypodermic needle after intramuscular injection has been rarely reported. We report a case of broken needle in the gluteal region in a 36 years old woman following an intramuscular injection. Patient arrived in the emergency after 2 days of the episode. Patient was taken for surgery for removal of the needle. Initially attempts for removal of needle were made without use of image intensifier under local anaesthesia, but it failed as it was very difficult to locate the needle. Patient was taken up for surgery under spinal anaesthesia with the use of image intensifier. Broken needle was located and removed. The following case describes the management of broken hypodermic needle and suggests valuable guidelines for minimising the chances of undue complications arising due to needle migration.